Probing hydrogen bonding orbitals: resonant inelastic soft X-ray scattering of aqueous NH3. Issue 40 (29th September 2015) - Weinhardt, L.; Ertan, E.; Iannuzzi, M.; Weigand, M.; Fuchs, O.; Bär, M.; Blum, M.; Denlinger, J. D.; Yang, W.; Umbach, E.; Odelius, M.; Heske, C.
Abstract : Resonant inelastic soft X-ray scattering was used to probe the hydrogen bonding orbitals in aqueous ammonia. Abstract : To probe the influence of hydrogen bonding on the electronic structure of ammonia, gas phase and aqueous NH3 have been investigated using soft X-ray absorption (XAS), resonant inelastic soft X-ray scattering (RIXS), and electronic structure calculations including dynamical effects. Strong spectral differences in the XAS scans as well as in the RIXS spectra between gas phase and aqueous NH3 are attributed to orbital mixing with the water orbitals, dipole–dipole interactions, differences in vibronic coupling, and nuclear dynamics on the time-scale of the RIXS process. All of these effects are consequences of hydrogen bonding and the impact of the associated orbitals, demonstrating the power of XAS and RIXS as unique tools to study hydrogen bonding in liquids.